Impact of Natural Polymer Proportions on the Fire-Retardant Properties of Bioplastics - Santhiarsa, I Gusti Ngurah Nitya; Dwidiani, Ni Made; Tenaya, I Gusti Ngurah Putu; Negara, I Gede Artha (Journal of Mechanical Engineering Science and Technology (JMEST), 2024)
This research investigates the influence of varying proportions of natural polymers on the fire-retardant properties of bioplastic. Tapioca starch (Manihot esculenta) and corn starch (Zea mays) were selected as the bioplastic materials, with different weight fractions employed in the analysis. These materials, as naturally occurring polymers, are biodegradable and serve as promising components in the development of bioplastics. Fire resistance testing was conducted in accordance with ASTM D635-03, utilizing weight ratios of tapioca to corn starch at 70:30, 60:40, and 50:50. The results included photographic documentation of each specimen alongside the corresponding outcomes from the fire resistance tests. These images provide insight into the physical condition of the specimens prior to testing, emphasizing any notable morphological features that may affect their fire resistance properties. The optimal burning rate was observed in the bioplastic with a 50:50 weight fraction ratio of tapioca starch to corn starch, which exhibited a combustion rate of 8.420 mm/s. Additionally, the bioplastic with the highest weight loss rate, recorded at 0.0346 g/s, was also composed of a 50:50 weight fraction of the two starches. The observed increase was 2.36% relative to the 60:40 weight fraction and 13% relative to the 70:30 weight fraction. This increased weight loss rate can be attributed to the higher corn starch content, which is characterized by inherent flammability due to its structural composition.